Cuscuta Chinensis potentiate the effect of methotrexate in Rheumatoid Arthritis Induced Rats. - Ahmed Shawqy Saadoon; Mustafa Ghazi Alabbassi; Nadia Hameed Mohammed (Al-Mustansiriyah Journal of Pharmaceutical Sciences, 2022)
Background